2019
DOI: 10.1038/s41419-019-1572-7
|View full text |Cite|
|
Sign up to set email alerts
|

Baicalein inhibits fibronectin-induced epithelial–mesenchymal transition by decreasing activation and upregulation of calpain-2

Abstract: The extracellular matrix protein fibronectin (FN) facilitates tumorigenesis and the development of breast cancer. Inhibition of the FN-induced cellular response is a potential strategy for breast cancer treatment. In the present study, we investigated the effects of the flavonoid baicalein on FN-induced epithelial–mesenchymal transition (EMT) in MCF-10A breast epithelial cells and in a transgenic mouse MMTV-polyoma middle T antigen breast cancer model (MMTV-PyMT). Baicalein inhibited FN-induced migration, inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…One of the ingredients is baicalein (BAI), which is commonly regarded as useful adjuvant therapeutic pharmaceutical for various diseases (6). Thus far, a number of researchers tested the efficacy of BAI on malignant tumors, such as breast carcinoma (7), non-small-cell lung carcinoma (8), cervical carcinoma (9), and carcinoma of urinary bladder (10). Moreover, previous research indicated that BAI impeded cell proliferation and melanogenesis of B16F10 mouse melanoma cells (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…One of the ingredients is baicalein (BAI), which is commonly regarded as useful adjuvant therapeutic pharmaceutical for various diseases (6). Thus far, a number of researchers tested the efficacy of BAI on malignant tumors, such as breast carcinoma (7), non-small-cell lung carcinoma (8), cervical carcinoma (9), and carcinoma of urinary bladder (10). Moreover, previous research indicated that BAI impeded cell proliferation and melanogenesis of B16F10 mouse melanoma cells (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies have shown that baicalein inhibits the invasion of cancer cells by inhibiting EMT through upregulating of calpain-2, inactivating the PI3K/Akt signaling pathway in B16F10 mouse melanoma cells, and suppressing 17B-estradiolinduced invasion via the G protein-coupled receptor 30 signaling pathway. [44][45][46] Herein, we demonstrated that baicalein reduced the F I G U R E 4 Baicalein suppresses FURIN and act-MT1-MMP by inhibiting the secretion of TGFB1 from EcESCs via the Smad3 pathway. A, ELISA was used to detect the levels of TGFB1 following treatment with baicalein for 48 h (n = 10).…”
Section: Discussionmentioning
confidence: 72%
“…On the contrary, Fibronectin (FN), a key component of the tumor ECM, seems to facilitate tumor formation, proliferation and angiogenesis. Its expression in breast tissue was positively correlated with an invasive and metastatic phenotype and negatively associated with survival and clinical outcome in breast cancer patients ( Chen et al, 2019 ). Thus these two genes could constitute privileged targets for the action of adipose cells leading to the loss of MEC function.…”
Section: Discussionmentioning
confidence: 99%